EFEKTIVITAS DAN EFISIENSI APLIKASI PEMBAYARAN TAGIHAN TERHADAP PENDAPATAN BULANAN INDIHOME PADA PT.TELEKOMUNIKASI,TBK WITEL MEDAN - Haura Novira Cahyani; Nur Fadhilah Ahmad Hasibuan (Worksheet : Jurnal Akuntansi, 2022)
Payment of receivables collection at PT. Telekomunikasi Indonesia (IndiHome) has a payment system that follows the times. Payment Collection is one part of the company that is in charge of processing monitoring and billing data for consumers who are negligent in making payments and making reports on billing evidence, reports of consumer internet disturbances and then input into the data system which will later be seen by the regional. This study aims to see which is more effective and efficient between cash payments and non-cash payments (digital). This study uses qualitative methods with primay data types. Based on the research results, IndiHome payment transactions, both cash and non-cash, have their respective advantages and disadvantages. IndiHome payments in cash can be said to be effective because customers get payment receipts in detail, clearly and transparently. However, cash payments cannot be said to be efficient because it uses such a long process. One of them is that customers have to come and queue to pay monthly for IndiHome and this can take a long time, requires energy and money. In contrast to non- cash payments (digital). Non-effective payments have not been said to be effective because of frequent errors in making payments such as different bills, bills that do not appear, and excess payments. However, for the efficiency of digital payments, it is said to be quite efficient because the payment process is quite easy and fast. Digital payments can be made anywhere and anytime.